If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y = 15 + -6x Solving 5y = 15 + -6x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '5'. y = 3 + -1.2x Simplifying y = 3 + -1.2x
| 4(r-3)+1=33 | | 5q+14=4 | | 13x+3+85+85+96=180 | | -1=d+21 | | 2(33+11x+3x)=c | | x^2+(-4x-14)(-4x-14)=25 | | (5q-2)+3-4q=4 | | 2(33+11x+3x)=x | | (x/4)-16=-32 | | 0.20x+7.5=0.27x+25 | | 6x+9y+10z=180 | | 3x+3.75= | | 14/5=7v | | (-4)=15-y | | (3x^2-2x+5)-(x^2+3x-2)=equation | | (x/4)-16= | | 5y/4=25 | | -(4x-2)=8x+26 | | .75x+15=13+.50x | | 18x-(8x-7)=66 | | 11=n/3=7 | | 7x+10x-6x-30=0 | | 7x-7=4x+25 | | 2x^2+8x+960=0 | | 5/21=-1/3k | | (-4x-14)(-4x-14)=0 | | 3x+12=x+25 | | -15=3/7x | | -.01x+60=x | | 20p+3q= | | 2v-12+2v=4v+1 | | 7w-3(4w+8)=39 |